PENGARUH PENGGUNAAN MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPS SISWA DI SD - Basir, Arief Haqqul; Marli, Suhardi; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to find out how much influence the use of Example Non Example model to the learning outcomes of IPS students of class III SDN 16 Pontianak Selatan